50. EVALUATION OF ACUTE TOXICITY OF SCORPION TURMERIC (CURCUMA RANGJUED)’S RHIZOME EXTRACTS FOR POTENTIAL MEDICINAL USE ON HUMANS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the acute toxicity of rhizome extracts of Curcuma rangjued on mouse model.Methodology: The acute toxicity testing was conducted in accordance with the OECD guideline 420 and the Vietnamese Ministry of Health's guidelines for preclinical and clinical trials of traditional and herbal medicines (Decision No. 141/QĐ-K2ĐT, released on 27 October, 2015).Results: Oral administration of Curcuma rangjued’s rhizome extracts at the dose of 5000 mg/kg did not induce acute toxicity in mice.Conclusions: Curcuma rangjued is a promising medicinal resource, proven to be safe and non-toxic at doses up to 5000 mg/kg body weight in experimental mice. Therefore, expanding the cultivation of Curcuma rangjued to harness this valuable medicinal resource could significantly contribute to public health.
Keywords: Curcuma rangjued; acute toxicity; mouse model; oral administration